Studi Penggunaan Natrium Valproat Kurang Dari Tiga Bulan Terhadap Magnesium Serum Dan Jumlah Kejang Pasien Epilepsi Di RSUD Dr. Soetomo - Latuasan, Ivana Rahayu; Sugianto, Paulus; Kasih, Elisabeth; Octavia, Evi (Jurnal Farmasi Sains dan Terapan, 2018)
Epilepsy is a brain disorder characterized by a tendency to cause continuous epilepsy attacks with neurobiological, cognitive, psychological and social consequences. The appearance of temporary signs or symptoms is caused by abnormal and excessive neuron activity in the brain. Sodium valproate can be used as epilepsy therapy because it is effective in inhibiting seizures, partial seizures, and tonic-clonic seizures. The mechanism of action of sodium valproate in the treatment of epilepsy is to increase the inactivation of Na + channels, thereby reducing the nerve's ability to transmit electric charges. Magnesium is a potential modulator of seizure activity because of its ability to inhibit excitation through N-methyl D-aspartate receptors. The aim of this study was to determine serum magnesium levels with sodium valproate treatment and the number of seizures as well as to identify drug-related problems in epilepsy patients who were less than three months old. The research was conducted in the Electroencephalography Room of the Regional Hospital Dr. Soetomo Surabaya by using observational methods in the form of prospective studies using data collection sheets and questionnaires. Samples were taken from July 1 to September 30, 2017. Based on laboratory results, the average magnesium content of patients with seizures was 2.22 mg / dL while non-seizure patients were 2.08 mg / dL. The conclusion of this study is that the use of sodium valproate does not affect magnesium levels in epilepsy patients and epilepsy patients who get sodium valproate therapy have a lower risk of seizures than those who do not get sodium valproate medication.